Cork oak (Quercus suber L.) seedlings acclimate to elevated CO2 and water stress: photosynthesis, growth, wood anatomy and hydraulic conductivity - Vaz, M; Cochard, H; Gazarini, L; Graça, J; Chaves, M M; Pereira, J S (Trees, 2012)
Leaf gas-exchange, leaf and shoot anatomy, wood density and hydraulic conductivity were investigated in seedlings of Quercus suber L. grown for 15 months either at elevated (700 lmol mol -1 ) or normal (350 lmol mol -1 ) ambient atmospheric CO2 concentrations. Plants were grown in greenhouses in a controlled environment: relative humidity 50% (±5), temperature similar to external temperature and natural light conditions. Plants were supplied with nutrients and two water regimes (WW, well watered; WS, water stress). After 6 months exposure to CO2 enrichment an increase in photosynthetic rate, a decrease in stomatal conductance and a decrease in carbon isotope discrimination (D 13 C) were observed, along with enhanced growth and an increase in the number of branches and branch diameter. Over the same period, the shoot weight ratio increased, the root weight ratio decreased and the leaf weight ratio was unaffected. The speciﬁc leaf area increased due to an increase in total leaf thickness, mainly due to the palisade parenchyma and starch. However, after 9 and 15 months of elevated CO2 exposure, the above-mentioned physiological and morphological parameters appeared to be unaffected. Elevated CO2 did not promote changes in vessel lumen diameter, vessel frequency or wood density in stems grown in greenhouse conditions. As a consequence, xylem hydraulic efﬁciency remained unchanged. Likewise, xylem vulnerability to embolism was not modiﬁed by elevated CO2. In summary, elevated CO2 had no positive effect on the ecophysiological parameters or growth of water stressed plants.
Keywords: Elevated CO2; Growth; hydraulic conductivity; Leaf and wood anatomy; photosynthesis; Quercus suber; Soil water stress

Azimuthal variations in xylem structure and water relations in cork oak (Quercus suber) - Čermák, Jan; Barij, Nadia; Stokes, Alexia (IAWA Journal, 2011)
Keywords: hydraulic conductivity; sap; vessel lumina; wood anatomy

Hydrological properties of cork container media - Carmona, E; Ordovas, J; Moreno, M T; Aviles, M; Aguado, M T; Ortega, M C (HORTSCIENCE, 2003)
Static hydrological properties \{[\}aeration capacity; easily available water, reserve water, water release curves: theta(v)(Psi(m)), and specific humidity curves] and dynamic hydrological properties (saturated and unsaturated hydraulic conductivity) of substrates based on industrial cork residue (the bark of Quercus suber L.) and cork compost were studied. Samples of similar granulometry have been used to establish the effect of cork composting on the aforementioned physical properties. Different models were tested to describe the mechanism of water release from these materials. Van Genuchten's model (Van Genuchten, 1978) was the best fit and produced specific humidity curves that revealed slight differences in the ratio of water capacity function. When cork residues were composted for 7 months, important changes occurred in hydrological properties of the material as it became more wettable. Water retention significantly increased from 45% to 54%, at a potential of 5 kPa, although this did not necessarily result in increased water available to plants. A study of the unsaturated hydraulic conductivity (K-unsat) of these materials revealed a significant decrease in the K-unsat water potential at 0-5 kPa, which corresponds to the range in which the irrigation with these substrates was usually carried out. The long composting process resulted in increased K-unsat between 4 and 5 times that of uncomposted material, which would improve the water supply to the plant.
Keywords: growing media; horticultural substrate; hydraulic conductivity; physical properties; water release curves

Hydrological properties of cork container media - Carmona, E.; Ordovas, J.; Moreno, M. T.; Aviles, M.; Aguado, M. T.; Ortega, M. C. (HORTSCIENCE, 2003)
Static hydrological properties \{[\}aeration capacity; easily available water, reserve water, water release curves: theta(v)(Psi(m)), and specific humidity curves] and dynamic hydrological properties (saturated and unsaturated hydraulic conductivity) of substrates based on industrial cork residue (the bark of Quercus suber L.) and cork compost were studied. Samples of similar granulometry have been used to establish the effect of cork composting on the aforementioned physical properties. Different models were tested to describe the mechanism of water release from these materials. Van Genuchten's model (Van Genuchten, 1978) was the best fit and produced specific humidity curves that revealed slight differences in the ratio of water capacity function. When cork residues were composted for 7 months, important changes occurred in hydrological properties of the material as it became more wettable. Water retention significantly increased from 45% to 54%, at a potential of 5 kPa, although this did not necessarily result in increased water available to plants. A study of the unsaturated hydraulic conductivity (K-unsat) of these materials revealed a significant decrease in the K-unsat water potential at 0-5 kPa, which corresponds to the range in which the irrigation with these substrates was usually carried out. The long composting process resulted in increased K-unsat between 4 and 5 times that of uncomposted material, which would improve the water supply to the plant.
The following values have no corresponding Zotero field: pub-location: 113 S WEST ST, STE 200, ALEXANDRIA, VA 22314-2851 USA publisher: AMER SOC HORTICULTURAL SCIENCE
Keywords: growing media; horticultural substrate; hydraulic conductivity; physical properties; water release curves

Seasonal embolism and xylem vulnerability in deciduous and evergreen Mediterranean trees influenced by proximity to a carbon dioxide spring - Tognetti, Roberto; Longobucco, Anna; Raschi, Antonio (Tree Physiology, 1999)
We investigated how proximity to natural CO2 springs affected the seasonal patterns of xylem embolism in Quercus ilex L., Quercus pubescens Willd., Fraxinus ornus L., Populus tremula L. and Arbutus unedo L., which differ in leaf phenology and wood anatomy. Xylem embolism was evaluated in both artificially dehydrated branches and in hydrated apical branches collected at monthly intervals during a 20-month sampling period. Initial specific hydraulic conductivity was also evaluated. We found species-dependent differences in xylem hydraulic properties in response to elevated CO2 concentration. Populus tremula was the most embolized and A. unedo was the least embolized of the species examined. Effects of elevated CO2 were significant in Q. pubescens, P. tremula and A. unedo, whereas the overall response to elevated CO2 was less evident in F. ornus and Q. ilex. Specific hydraulic conductivity differed among species but not between sites, although the interaction between species and site was significant. Differences in xylem vulnerability between trees growing near to the CO2 spring and those growing in control areas were small. Although differences in hydraulic properties in response to elevated CO2 concentration were small, they may be of great importance in determining future community composition in Mediterranean-type forest ecosystems. The possible causes and ecological significance of such differences are discussed in relation to elevated CO2 concentration and other environmental conditions.
10.1093/treephys/19.4-5.271
Keywords: cavitation; CO2 springs; diffuse-porous; Global change; hydraulic conductivity; Mediterranean-type ecosystems; ring-porous; semiring-porous

Different vulnerabilities of Quercus ilex L. to freeze- and summer drought-induced xylem embolism: an ecological interpretation - Lo Gullo, M. A.; Salleo, S. (Plant, Cell & Environment, 1993)
Quercus ilex L. growing in the southern Mediterranean Basin region is exposed to xylem embolism induced by both winter freezing and summer drought. The distribution of the species in Sicily could be explained in terms of the different vulnerability to embolism of its xylem conduits. Naturally occurring climatic conditions were simulated by: (1) maintaining plants for 3h at ambient temperatures of 0, -1.5, -2.5, -5.0 and -11°C; and (2) allowing plants to dry out to ratios of their minimum diurnal leaf water potentials (Ψ1) to that at the turgor loss point (Ψtlp) of 0.6, 0.9, 1.05, 1.20 and 1.33. The loss of hydraulic conductivity of one-year-old twigs reached 40% at -1.5°C and at Ψ1/ΨtlP= 1.05. Recovery from these strains was almost complete 24 h after the release of thermal stress or after one irrigation, respectively. More severe stresses reduced recovery consistently. The percentages of xylem conduits embolized following application of the two stresses, were positively related to xylem conduit diameter. The capability of the xylem conduits to recover from stress was positively related to the conduit diameter in plants subjected to summer drought, but not in the plants subjected to winter freezing stress. The ecological significance of the different vulnerabilities to embolism of xylem conduits under naturally occurring climatic conditions is discussed.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: conduit diameter; Fagaceae; holm-oak; hydraulic conductivity; Quercus ilex L.; summer drought; winter freezing; xylem embolism

Different vulnerabilities of Quercus ilex L. to freeze- and summer drought-induced xylem embolism: an ecological interpretation - LO GULLO, M A; Salleo, S (Plant, Cell & Environment, 1993)
Quercus ilex L. growing in the southern Mediterranean Basin region is exposed to xylem embolism induced by both winter freezing and summer drought. The distribution of the species in Sicily could be explained in terms of the different vulnerability to embolism of its xylem conduits. Naturally occurring climatic conditions were simulated by: (1) maintaining plants for 3h at ambient temperatures of 0, -1.5, -2.5, -5.0 and -11°C; and (2) allowing plants to dry out to ratios of their minimum diurnal leaf water potentials (Ψ1) to that at the turgor loss point (Ψtlp) of 0.6, 0.9, 1.05, 1.20 and 1.33. The loss of hydraulic conductivity of one-year-old twigs reached 40% at -1.5°C and at Ψ1/ΨtlP= 1.05. Recovery from these strains was almost complete 24 h after the release of thermal stress or after one irrigation, respectively. More severe stresses reduced recovery consistently. The percentages of xylem conduits embolized following application of the two stresses, were positively related to xylem conduit diameter. The capability of the xylem conduits to recover from stress was positively related to the conduit diameter in plants subjected to summer drought, but not in the plants subjected to winter freezing stress. The ecological significance of the different vulnerabilities to embolism of xylem conduits under naturally occurring climatic conditions is discussed.
Keywords: conduit diameter; Fagaceae; holm-oak; hydraulic conductivity; Quercus ilex L.; summer drought; winter freezing; xylem embolism